An energy future beyond climate neutrality: Comprehensive evaluations of transition pathways. (1st February 2023) - Martin, Nick; Talens-Peiró, Laura; Villalba-Méndez, Gara; Nebot-Medina, Rafael; Madrid-López, Cristina
Graphical abstract: Highlights: Energy models generally fail to consider impacts beyond direct GHG emissions. ENBIOS joins a push to integrate life cycle thinking into energy modelling frameworks. Extra dimensions are added via social metabolism and hierarchical analysis. Analysis of EU scenarios reveals potential land use, labour and material issues. Abstract: Many of the long-term policy decisions surrounding the sustainable energy transition rely on models that fail to consider environmental impacts and constraints beyond direct greenhouse gas emissions and land occupation. Such assessments offer incomplete and potentially misleading information about the true sustainability issues of transition pathways. Meanwhile, although decision-makers desire greater access to a broader range of environmental, material and socio-economic indicators, few tools currently address this gap. Here, we introduce ENBIOS, a framework that integrates a broader range of such indicators into energy modelling and policymaking practices. By calculating sustainability-related indicators across hierarchical levels, we reach deeper understandings of the potential energy systems to be derived. With ENBIOS, we analyse a series of energy pathways designed by the Calliope energy system optimization model for the European energy system in 2030 and 2050. Although overall emissions will drop significantly, considerable rises in land, labour and critical raw material requirements are likely. These outcomes are further reflected in unfavourable shifts in key metabolic indicators during this period; energy metabolic rate of the system will drop by 25.6%, land requirement-to-energy will quadruple, while the critical raw material supply risk-to-energy ratio will rise by 74.2%. Heat from biomass and electricity from wind and solar are shown to be the dominant future processes across most indicator categories.